The Old Man’s Advances — about Idyll Chloe and Likas Wrotten by Franciszek Zabłocki - Prokopczyk, Beata (Starość i młodość w literaturze i kulturze, 2016)
This article is about rococo realisation of the motif of old age in one of the idyll, written by FranciszekZabłocki (1752–1821), which appeared in print in the volume “Zabawy Przyjemne i Pożyteczne” at thebeginning of April 1775. The analysed work, en titled Chloe and Likas, is about an old man who makesadvances to young and beautiful girl and he must compete with younger rival. This idyll is based ondialogue, in which main characters deliberate on relationships between love and age, rule of the humanlife and attributes of old age and youth. I will analyse the way of writing about old age and youth andperceiving this two stages in of life by the Enlightenment poet.